INFORMATION WEBSITE DESIGN FILM, NOVEL AND MUSIC USING DREAMWEAVER MX 2004 - Indah Permatasari Cahyaningtyas; Ire Puspa Wardhani, S.Kom.,MMSI (Jurnal Sistem Informasi, 2005)
Today technology is growing rapidly, where human needs information superhighway. Especially with the internet facility which began ogled as a media campaign that was quite interesting. To that end, the author wants to provide news and information about the film in particular, and little additional information about the novel and the new album of new music in circulation to the users who want to know the latest information from the above - mentioned above. The site is expected to make it easy for people - people who need information about movies, novels and music without having to visit the cinema or bookstore and record store. And also this site is created by using the Indonesian language so that the users will be more easily understood.